MCM wines in China : taking on the dragon - Townsend, Stephanie (SAGE knowledge. Cases., 2016)
In July 2009, businessman and entrepreneur, Martyn Mills of MCM Wines, reconsidered his marketing strategy. He had been exporting his own wine to China since 2003 and had recently signed an agreement with the prestigious South African wine estate, Groot Constantia, to export its wine to that country as well. However, conducting business in China was complex and expensive and, earlier that year, he had partnered with a new importer in China to help combat certain of the challenges. Mills wanted to support his new business partner as much as he could in promoting MCM wines; however, he had a limited budget. Given this fact, how could he grow his market in China, he wondered?